"Arise Ye Wretched of the Earth": The First International in a Global Perspective - Bensimon, Fabrice; Deluermoz, Quentin; Moisand, Jeanne (Studies in Global Social History, 2018)
"Arise Ye Wretched of the Earth" provides a fresh account of the International Working Men's Association. Founded in London in 1864, the First International gathered trade unions, associations, co-operatives, and individual workers across Europe and the Americas. Readership: All interested in the worker's history. Academic libraries would also be interested. Post-graduate and undergraduate students.